Tuning the hysteresis of a metal-insulator transition via lattice compatibility - Y. G. Liang (Nature Portfolio, 2020)
The effect of the lattice degrees of freedom on the metal-insulator transition of VO2 remains a topic of debate. Here the authors show that the lattice compatibility of the high temperature tetragonal phase and the low-temperature monoclinic phase strongly influences the electronic transition, as manifested in the tunability of its hysteresis via chemical substitution.